Accuracy of 7-8-9 Rule for Endotracheal Tube Placement in Nepalese Neonates - Paudel, KP; Nepal, D; Mahaseth, C (Journal of Nepal Paediatric Society, 2011)
Introduction: Neonatal intubation is done for cardiopulmonary resuscitation, hypoxemia, and hypercapnia, for surfactant therapy or for airway protection. When correctly placed, endotracheal tube (ETT) tip should be at mid tracheal position which is half way between the clavicles and the carina to prevent complications of ventilation. Objective: To assess the accuracy of 7-8-9 Rule in neonates at Kanti Children’s hospital. Methodology: Prospective observational study was conducted in neonates who required oral intubations from July 2009 to December 2009 at NICU of Kanti Children’s Hospital. The initial ETT depth of insertion was determined using admission weight in the 7-8-9 Rule calculation. This depth was compared to the midtracheal depth to determine clinical accuracy of the 7-8-9 Rule. Results: Mean gestation age of the 69 infants was 36.01 weeks (26 to 42 weeks) and weight was 2411 g( 900 g to 3800 g ). 7 (10.1%) neonates weighed 1000 g or less, 19 (27.5%) weighed between 1001 to 2000 g, 31 ( 44.9%) weighed between 2001 to 3000 g, 12(17.4%) weighed between 3001 to 4000 g. The accuracy of 7-8-9 rule in clinical setting with auscultation and Chest x-ray resulted in ETT depth 0.11 cm above midtracheal position. (-1.5 to 1.5 cm). Using this rule ET tube was placed 0.11 cm above the mid tracheal position. Conclusions: The 7-8-9 Rule appears to be an accurate clinical method for endotracheal tube placement in Nepalese neonates. Keywords: Intubation; Neonate; Mid Tracheal Position DOI: http://dx.doi.org/10.3126/jnps.v31i3.4299 J Nep Paedtr Soc 2011;31(3): 175-179